Breast hypertrophy, forward head posture, neck and shoulder pain-related disabilities and selected anthropometrics variables of female undergraduate students - Akodu, Ashiyat Kehinde; Oti, Temiloluwa Grace; Lawal, Abdulrazzaq Oluwagbemiga (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Large breast sizes frequently contribute to women presenting with severe pain symptoms. This study determined the association between breast hypertrophy, forward head posture (FHP), neck and shoulder pain related disabilities and selected anthropometric variables of female undergraduate students of College of Medicine, University of Lagos. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A cross-sectional analytical study was conducted among 89 female undergraduate students (mean age = 21.45±1.29 years) with breast hypertrophy (cup size D and above). Breast cup sizes, neck and shoulder pain related disabilities, forward head posture were measured using a measuring tape, neck pain disability scale, shoulder pain disability index and craniovertebral angle (CVA) using photography method. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The prevalence of forward head posture among the participants was 43(48.3%). Twenty-eight (31.3%) participants had a “DD” cup size, twenty-six (29.2%) participants had a “DDD” cup size. Sixty-five (73%) of the participants had neck pain related disabilities and 10 (11.2%) of the participants had shoulder pain related disabilities. There was association among weight, forward head posture (p=0.027) and breast hypertrophy (p=0.016). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Neck, shoulder pain related disabilities, and forward head posture is prevalent among undergraduates with breast hypertrophy and weight has an influence on forward posture and breast hypertrophy.